The five-year KRAS, NRAS and BRAF analysis results and treatment patterns in daily clinical practice in Slovenia in 1st line treatment of metastatic colorectal (mCRC) patients with RASwild-type tumour (wtRAS) - Mesti, Tanja (Radiology and oncology (Ljubljana), 2023)
Background. We preformed a Phase IV non-interventional study to assess KRAS, NRAS and BRAF status in metastatic colorectal cancer (mCRC) patients suitable for 1st line treatment and to evaluate the decisions for 1st line treatment considering the treatment goals in the RAS wild type (wt) patients. The aim of our study was also to evaluate the influ-ence of a waiting period for biomarkers analysis on the start of first-line treatment.Patients and methods. Patients with histologically confirmed mCRC adenocarcinoma suitable for first-line treat-ment fulfilling all inclusion criteria were included in the study. The KRAS, NRAS and BRAF analysis was performed from tissue samples of primary tumor site or metastatic site. All included patients have given consent to participate in the study by signing the informed consent form. Results. From April 2013 to March 2018 at the Institute of Oncology Ljubljana 650 patients were included, 637 of them were treated with first- line systemic treatment according to RAS and BRAF status. Remaining 13 patients with mCRC did not receive systemic first-line treatment. The distribution of patients with KRAS mutated and wild-type tumors, was almost equal, 48.8% and 47.9% respectively, 89 % of the patients had wt NRAS tumours and 86.1% had wt BRAF tu-mours. The most frequently prescribed treatment was bevacizumab-based therapy (53.1%), either in combination with doublet chemotherapy or with mono-chemotherapy. EGFR inhibitors cetuximab and panitumumab were prescribed in wt RAS mCRC patients (30.9%). The waiting period for biomarkers analysis was two weeks.Conclusions. Our real-world data, single centre 5-year analysis showed that the distribution between wild type and mutated type tumors of the patients with mCRC was approximately the same, as worldwide, so the Slovenian popula-tion with mCRC has the same ratio distribution of KRAS, NRAS and BRAF wild and mutated genes. We concluded that a two-week waiting period for biomarkers analysis did not influence the first line treatment decision, so it was in the accordance with the worldwide treatment guidelines based on evidence-based medicine.
Keywords: biološki označevalci RAS in BRAF; metastatic colorectal cancer; metastatski rak; rak debelega črevesa in danke; RAS and BRAF biomarkers; sistemsko zdravljenje; systemic treatment